Multipath joint ablation strategy for focal atrial tachycardia originating from patent foramen ovale: a case report - Liu, Fuqiang; Li, Yifei; Yan, Song; Liu, Lijun; Zhou, Kaiyu; Hua, Yimin (Frontiers in Cardiovascular Medicine, 2025)
IntroductionFocal atrial tachycardia (FAT) is predominant in the pediatric population. Recent research has identified cases of sustained FAT originating from the interatrial septum (IAS); a subset of cases presents a unique challenge, with foci originating from the peri-patent foramen ovale (peri-PFO), requiring specialized management during catheter ablation. Here, we present a rare case of peri-PFO-associated FAT that resulted in tachycardia-related cardiomyopathy and propose a comprehensive multipath joint strategy for the successful treatment of PFO-associated FAT.Case presentationA 10-year-old boy presented with refractory cardiomyopathy associated with incessant atrial tachycardia, unresponsive to metoprolol. A 12-lead electrocardiogram revealed a narrow QRS complex tachycardia with a rate of 157 beats per minute and a prolonged RP relationship. Echocardiography indicated a severely reduced ejection fraction of 22%. Subsequent electrophysiological study findings identified the tachycardia as originating from the anterior limbus of the PFO. Radiofrequency ablation was performed at the earliest activation site and surrounding structures, encompassing the right atrial septum, non-coronary sinus of Valsalva, and the left atrium peri-PFO. Post-procedure, the patient remained free from arrhythmia and showed restored normal cardiac function and was prescribed a low-dose β-blocker for 1 month. Remarkably, the patient continued to be well without the need for any medications for the subsequent 3 months.ConclusionThe structure of the PFO brought significant challenges in performing successful ablation. The multipath strategy was beneficial in managing peri-PFO-associated FAT based on its anatomical vicinity of the target.